Investigation of particulate matter and combustion characteristics of a diesel engine fueled with palm oil methyl ester and diesel blends - Ahmad Fitri, Yusop (2015)
Diesel engines are attractive power units that are used widely in many fields and have become one of the larger contributors of total petroleum consumption. However, diesel engines are among the main contributors to emissions into the air, especially particulate matter (PM) and nitrogen oxides (NOx). PM is one of the major pollutants emitted by diesel engines and has adverse effects on human health. However, not many studies have been conducted on the PM concentration and PM morphological and size distribution on biodiesel fuel. Biodiesel, which produces less PM than diesel fuel, is preferred as an alternative source for diesel engines. Therefore, using palm oil methyl ester (POME) for diesel engines would be a more economical and sustainable solution. The objective of this research is to study the PM emissions characteristic from diesel engines fuelled with a diesel and POME blend. A transmission electron microscope (TEM) was used to determine the aggregate fractal prefactor, spherule, and aggregate size distribution. A comparison between diesel and the POME blend was made in terms of PM characterization, which involves PM mass concentration, its components soluble organic fraction (SOF) and dry soot (DS), and its influence on PM morphology such as spherule and aggregate correlation. Combustion characteristics such as in-cylinder pressure and rate of heat release of the engine as well as gaseous emissions were also observed at different operating engine loads. The results show that PM emissions of B100 are lower than those of diesel fuel owing to the oxygen content of POME. Observations of images on PM morphology showed a chainlike agglomeration, which is an extremely small non-uniform nanostructure. Simultaneously, the aggregate size distribution shifted to a smaller diameter as the blending ratio of POME in the fuel increased. The observation of in-cylinder pressure showed that the increment of pressure with the increasing POME blend as well as the increasing engine load is due to high cetane number for B100 that led to a shorten ignition delay. The engine brake thermal efficiency between the POME blend and mineral diesel was comparable. Furthermore, B100 fuels showed lower engine power at higher brake-specific fuel consumption compared to other tested fuels. In terms of gaseous emissions, increasing POME blends led to an increase in CO2 and NOx while decreasing CO emission. Meanwhile, as the engine load increased, CO2, NOx and CO also continued to increase. The effect of the POME blend on the PM-NOx trade-off observation showed that B100 simultaneously increased the NOx and decreased the PM emission. Both the wavelet analysis and coefficient of variation revealed that increasing the POME ratio provided a noticeable effect on increasing the engine cycle-to-cycle variations. It can be concluded that POME creates lower PM concentration while giving some negative feedback to NOx and resulting in smaller particle size. Moreover, the findings reveal that by having the wavelet analysis, one can predict the behavior of the PM emissions and subsequently further research helps to reduce them effectively and economically.